FORMATION OF INFORMATION HYGIENE OF YOUNG PEOPLE THROUGH THE PRISM OF MEDIA LITERACY - Rudenko, Yuliia (Physical and Mathematical Education, 2023)
The article touches upon the problem of the formation of information hygiene of young people through the prism of the younger generation’s media literacy (info media literacy). The author’s workshop for the development of information hygiene skills is described. Formulation of the problem. Society is aware of the magnitude of the impact of information technology on the psyche, behavior, preferences, and values of citizens. Therefore, the problem of forming media literacy in the population to prevent destructive political, social, and other processes is actualized. Materials and methods. Analysis of scientific sources to identify the state of elaboration of the problem. Modeling, pedagogical experiments, and surveys to test the workshop’s effectiveness. The experiment involved 64 1st year students of Sumy National Agrarian University and Makarenko Sumy State Pedagogical University. Results. The importance of developing personal qualities for young people is proven: critical thinking of young people regarding the consumption, verification, and evaluation of media products; the ability to resist manipulation, destructive influences, and hostile propaganda; development of a culture of interaction in the Internet space and the ability to protect their own information space. The author’s workshop and methods of its conduct are described. Conclusions. An essential condition for the workshop’s success is interactivity, game methods, teaching techniques of emotional relief, learning from examples, and actual media products. For the practicum, a logical sequence of classes is essential (motivation, encouragement to study, teaching practical techniques, checking the results, reflection), the use of interactive and game methods (quizzes, contests, training, master classes), learning from real examples, actual media products. The workshop showed significant positive changes in the ability to distinguish facts from judgments, to identify inaccurate information that can be used to develop courses of free choice for students or to organize webinars focused on developing information hygiene for young people.